2008
DOI: 10.1002/chem.200801129
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Magnesium(II) Coordination Polymeric Hydrogel

Abstract: A pH and mechano-responsive coordination polymeric gel was developed without the use of long chain hydrophobic groups. The hydrogel was synthesised by reacting the aqueous solution of Mg2+ with the basic aqueous solution of N-(7-hydroxyl-4-methyl-8-coumarinyl)-alanine. The gelation is attributed to the self-aggregation of 1D coordination polymers to form 3D nanostructures through non-covalent interactions to entrap water molecules. The freeze-dried hydrogel exhibits a fibrillar network structure with a uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 78 publications
3
47
0
Order By: Relevance
“…In fact, crystal engineering of numerous luminescent MOFs and CPs has been reported, aiming at their use in (opto)electronic applications [109,111,122,290,291]. As a result of these studies, it was observed that some morphologies of MOFs containing Eu 3+ or Tb 3+ are correlated with a lower number of defects, which leads in turn to enhanced fluorescent intensity [92,292].…”
Section: Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, crystal engineering of numerous luminescent MOFs and CPs has been reported, aiming at their use in (opto)electronic applications [109,111,122,290,291]. As a result of these studies, it was observed that some morphologies of MOFs containing Eu 3+ or Tb 3+ are correlated with a lower number of defects, which leads in turn to enhanced fluorescent intensity [92,292].…”
Section: Applicationsmentioning
confidence: 96%
“…[(Ag-2)NO3]n fibers 9 b) [112] ZIF-8 hexagonal 40 [62] [ [122] [SnT(4-Py)PCl2]n spheres 116.7 [114] [[Ni(TBA)(m-BPY)]·BPY]n fibers 100 b) [115] [Zn(BIBP)2(OSO2CF3)2]n sheets 2-3·10 3 [123] [Ag(L1)NO3]n rods 20-30 [94] [ [100]…”
mentioning
confidence: 99%
“…26) [61]. The carboxylate oxygen atoms of 23 coordinated to the neighboring Copyright Wiley-VCH Verlag GmbH and Co. KGaA.…”
Section: Static Coordination Polymer Gelsmentioning
confidence: 99%
“…Reproduced with permission from ref. [61]. metal center to form the coordination polymer 24, shown in Fig.…”
Section: Static Coordination Polymer Gelsmentioning
confidence: 99%
“…The poor solubility of the polymer chains in common solvent makes it difficult to study the interaction between coordination polymer and solvent. [6][7][8][9] Up to now, only few soluble coordination polymers have been synthesized through the introduction of bulky substituent on the backbone, with adamant or dendron side chains, to prevent chain aggregation and improve polymer-solvent interactions. [10][11][12][13] The conformations and self-assembly of soluble coordination polymers are greatly influenced by the properties of the bulky side-chains, solvent polarity and temperature.…”
Section: Introductionmentioning
confidence: 99%